Fifteen-minute consultation: approach to a child with congenital insensitivity to pain - Anuar, Muhamad Azamin; Whitehouse, Emily Rose; Varma, Uma; McCullagh, Gary; Hughes, Imelda (BMJ Publishing Group, 2025)
The hereditary sensory and autonomic neuropathies (HSANs) are a group of rare genetic disorders characterised by variable phenotypic expression affecting both sensory and autonomic dysfunction. Diagnosing these conditions can be a challenge as the presenting symptoms can be diverse and may overlap. This often leads to a delay in referral and diagnosis. Pain is often used by clinicians as a marker for systemic diseases. The key feature of HSAN conditions is the absence of pain perception and its consequences such as unexplained injuries. When a child presents with an unexplained injury, a diagnosis of non-accidental injuries must be considered, but rarely HSAN could be a possibility. The diagnosis of HSANs in children is both important and rare. This article aims to discuss an approach to the diagnosis and management of HSANs